The Perception and Readiness of Nursing Higher Education Institutions in the Implementation of Outcome Based Education Curriculum - Widyatuti, Widyatuti; Jauhar, Muhamad (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2022)
Introduction: Graduates of higher education are expected to be able to answer the challenges and needs of the business world and the development of social life. The OBE (Outcome Based Education) curriculum is a learning approach that focuses on student competencies and is based on outcomes. The OBE curriculum is expected to be applied in the curriculum of higher nursing education in Indonesia to answer these challenges. This study aims to describe the perceptions and readiness of nursing higher education institutions in implementing that  curriculum.    Methods: The Research uses a descriptive quantitative design with a cross-sectional approach. Research is conducted in the nursing higher education institutions of AIPNI (Asosiasi Institusi Pendidikan Ners Indonesia/The Association Of Indonesian Nurses Education)  members spread over 13 regionals of Indonesia from May- September 2022. The research sample is 108 institutions through the purposive sampling technique. Inclusion criteria are institutions registered as active members of AIPNI. The variables of this research are perception and readiness of institution education in implementing the OBE curriculum. The research instrument uses a perception and readiness questionnaire of OBE with a reliability score = 0.919. Data analysis uses descriptive frequency. This research had passed the ethical review from the Research Ethics Committee of the Faculty of Nursing, University of Indonesia Number: KET-190/UN2.F12.D1.2.1/PPM.00.02/2022.  Results : The results showed that the Head of  Nursing Profession Program was 41.05 years old, the SD was 7,844 and 80 (74.1%) had master’s degree. Half of the heads of the nursing professional education study program have a poor perception of the implementation of the results-based curriculum as many as 58 people (51.9%) and have poor readiness about the implementation of the results-based curriculum as many as 54 people (50%).Conclusions : The Heads of Nursing Profession Program have a poor perception and readiness in implementing the OBE curriculum. The results of this research become the basic data in determining policies for the OBE curriculum implementation, especially at the level of nursing profession program. Socialization and guidance from association of educational institution is needed, that nursing higher education institutions have similar perception and readiness in implementing the OBE curriculum.